Recurrent gain of function mutation in calcium channel CACNA1H causes early-onset hypertension with primary aldosteronism - Scholl, Ute I; Stölting, Gabriel; Nelson-Williams, Carol; Vichot, Alfred A; Choi, Murim; Loring, Erin; Prasad, Manju L; Goh, Gerald; Carling, Tobias; Juhlin, C Christofer; Quack, Ivo; Rump, Lars C; et al. (eLife, 2015)
Many Mendelian traits are likely unrecognized owing to absence of traditional segregation patterns in families due to causation by de novo mutations, incomplete penetrance, and/or variable expressivity. Genome-level sequencing can overcome these complications. Extreme childhood phenotypes are promising candidates for new Mendelian traits. One example is early onset hypertension, a rare form of a global cause of morbidity and mortality. We performed exome sequencing of 40 unrelated subjects with hypertension due to primary aldosteronism by age 10. Five subjects (12.5%) shared the identical, previously unidentified, heterozygous CACNA1HM1549V mutation. Two mutations were demonstrated to be de novo events, and all mutations occurred independently. CACNA1H encodes a voltage-gated calcium channel (CaV3.2) expressed in adrenal glomerulosa. CACNA1HM1549V showed drastically impaired channel inactivation and activation at more hyperpolarized potentials, producing increased intracellular Ca2+, the signal for aldosterone production. This mutation explains disease pathogenesis and provides new insight into mechanisms mediating aldosterone production and hypertension. The consequence of mutations to the large majority of human genes is unknown. Most mutations that are currently known were discovered by tracing their effects through families. This allows the locations of mutations to be pinpointed on chromosomes—the structures that genetic material is packaged into. Other mutations are harder to trace because individuals with these mutations may develop very different signs and symptoms, or not develop clinical abnormalities at all. Alternatively, a trait may appear sporadically in a family because the mutation arises anew in the affected subject. Recently developed technologies that allow scientists to rapidly sequence all the gene-encoding regions of an individual's DNA—their genome—offer a new way to identify harmful genetic variants. Comparing the genomes of individuals with rare disorders can reveal if the individuals share any genetic mutations in common that could cause their symptoms. Scholl et al. used this strategy to sequence the genomes of 40 individuals with a rare type of hypertension—a condition that causes high blood pressure, and increases the risk of strokes, kidney failure and heart attacks—that develops early in childhood. In this form of the disease, high blood pressure is caused by the adrenal glands above the kidneys producing too much of a hormone called aldosterone. Some genetic causes of this form of the disease have already been identified. Now, Scholl et al. have found a new genetic mutation present in five families with this condition. Two of the individuals were the first in their families to develop this mutation, while three others inherited it. Some of the family members with this mutation had hypertension and some did not. The mutation is in a gene that encodes a type of calcium channel—a protein found in the membrane that surrounds cells, and which can open and close to control the amount of calcium in the cell. This particular calcium channel is abundant in the cells of the adrenal gland. Scholl et al. found that the mutation causes the calcium channels to be more likely to open and take longer to close. This increases the number of calcium ions that move into the cell, which causes the adrenal gland to produce more aldosterone. These new insights have provided a new way of diagnosing early-onset hypertension, and suggest that targeting calcium channels could help to develop new treatments for this disease.